2011
DOI: 10.3390/s110605850
|View full text |Cite
|
Sign up to set email alerts
|

The New Seafloor Observatory (OBSEA) for Remote and Long-Term Coastal Ecosystem Monitoring

Abstract: A suitable sampling technology to identify species and to estimate population dynamics based on individual counts at different temporal levels in relation to habitat variations is increasingly important for fishery management and biodiversity studies. In the past two decades, as interest in exploring the oceans for valuable resources and in protecting these resources from overexploitation have grown, the number of cabled (permanent) submarine multiparametric platforms with video stations has increased. Prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 46 publications
0
57
0
Order By: Relevance
“…During these times, however, almost no information is available in most Arctic fjord systems (Kwasniewski, 2003). Understanding polar ecosystems in the context of global warming and expected or already observed ecosystem changes (Müller et al, 2011;Bartsch et al, 2016) is, however, crucial for thoroughly understanding the ecosystem behaviour in polar areas.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…During these times, however, almost no information is available in most Arctic fjord systems (Kwasniewski, 2003). Understanding polar ecosystems in the context of global warming and expected or already observed ecosystem changes (Müller et al, 2011;Bartsch et al, 2016) is, however, crucial for thoroughly understanding the ecosystem behaviour in polar areas.…”
Section: Discussionmentioning
confidence: 99%
“…This bi-modal hydrographic situation leads to a complex spatio-temporal pattern in the fjord hydrography with an occasionally more Atlantic and in other instances more Arctic characteristic with respect to the water masses, even in the inner fjord system (Svendsen et al, 2002). Due to an increased advection rate of warmer Atlantic water masses in the fjord systems over the last decade (Cottier et al, 2005), the first signs of an overall warming of the fjord system have been observed, with an overall decrease in seasonal ice coverage (Walczowski et al, 2012), signifi- cant changes in the phytoplankton community (Hegseth and Tverberg, 2013;Willis et al, 2006), changes in the depth distribution of macroalgae in the shallow waters (Bartsch et al, 2016) and in the macrozoobenthos community (Parr at al., 2015), as well as an increase in turbidity due to increased meltwater runoff from the glaciers (Peterson et al, 2002;Bartsch et al, 2016). Although Renaud et al (2011) and Voronkov et al (2013) recently started to study the foodchain length, trophic levels, and the main feeding groups in Kongsfjorden, our knowledge of the temporal and spatial dynamics of the higher trophic levels of the food web is still extremely limited (Stempniewicz et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The intervention tasks to be demonstrated include docking to a custom sub-sea panel, fixed-based manipulation for both valve turning and hot stab connection, and free floating manipulation for camera dome de-fouling. The final demonstration will be carried out in the OBSEA (Aguzzi et al (2011)) expandable seafloor observatory cabled to the shoreline in the Catalan coast. The final experiments plan to demonstrate high bandwidth data communication between the I-AUV and the observatory and from it to the world wide web through the observatory web page.…”
Section: Triton 2012-14mentioning
confidence: 99%